Quality of follow-up monitoring of the adult population with grade 1-3 hypertension, with the exception of resistant hypertension, by primary care physicians in different Russian regions - O. M. Drapkina; R. N. Shepel; L. Yu. Drozdova; A. M. Kalinina; E. S. Bulgakova; D. O. Orlov; I. V. kurilov (Российский кардиологический журнал)
In view of the high prevalence of hypertension (HTN) among Russian population, it becomes extremely important to meet the criteria for the medical care quality within the periodic examinations for this group of patients.Aim.  To assess the quality of follow-up monitoring of the adult population with grade 1-3 hypertension, with the exception of resistant hypertension (RH), by primary care physicians in different Russian regions.Materials and methods. As part of working visits of the expert group from the National Medical Research Center for Therapy and Preventive Medicine in 38 Russian regions in the period from February 1, 2020 to December 15, 2020, an analysis of ambulatory records of patients with grade 1-3 hypertension was carried out. A total of 3614 ambulatory medical records (AMRs) were analyzed, of which the grade 1-3 hypertension, with the exception of RH, was revealed in 764 ones. The analysis of records was carried out using an original checklist. Statistical processing was carried out using the software package IBM SPSS Statistics 20 (USA) and Microsoft Office Excel 2016 (USA).Results. An analysis of 764 AMRs was performed. The mean age of patients was 63,9-11,2 (women, 64,7-11,3 years; men, 62,7-10,9 years). The majority (58,9%) of participants were women. Follow-up monitoring was established in a timely manner in 450 people (58,9%) of patients, of which there were 189 men (42%) and 261 women (58%). In 87,9% (n=672) of cases, the diagnosis formulation met the established clinical guidelines criteria. In 36 cases (4,7%), there was no evidence in favor of hypertension according to the current clinical guidelines. In 21,1% (n=161) of cases, the minimum recommended periodicity of visits was not observed. In last visits of 323 patients, the blood pressure did not reach the target values. AMRs did not contain information on low-density lipoprotein cholesterol (LDL-C) in 91б4% of cases (n=698). Among patients with a known level of LDL-C, the target values were achieved only in 15,2% of cases (n=10).Conclusion. Our analysis revealed the insufficient quality of outpatient medical care to hypertensive patients within the periodic examinations. Proposals are created for monitoring and measures to improve the quality of care for this category of patients.